First Report of a Case of Pneumococcal Meningitis Which Did Not Respond to the Ceftriaxone Therapy despite the Isolated Organism Being Sensitive to This Antibiotic In Vitro - Maryam Mojtabavi; Hamid Reza Naderi; Ashraf Tavanaee Sani; Mahmood Bagheri; Kiarash Ghazvini (Case Reports in Pulmonology)
A 60-year-old man presented with pneumococcal meningitis which did not respond to the ceftriaxone therapy, in spite of in-vitro susceptibility (minimal inhibitory concentration of 0.016 μg/dLit) of the isolated organism to this antibacterial agent, although ceftriaxone is still the drug of choice for such pneumococcal meningitis. Review of published articles revealed no report of clinical resistance in organisms which were susceptible to the same antimicrobial agent in vitro. This alarming emergence of isolates with in vivo resistance should be considered and even could lead to a shift in the empirical antibiotic therapy for pneumococcal infections.